Объяснение:
А
А) z1 = (2a+b)(2-i) = (4a+2b) - (2a+b)i
Комплексно
Комплексно сопряжённое:
~z1 = (4a+2b) + (2a+b)i
z2
z2 = (a+b+1) - (2a+2)i
Если
Если ~z1 = z2, то:
{ 4a + 2b = a + b + 1
{ 2a + b = - (2a + 2) = -2a - 2
Приводим
Приводим подобные:
{ 3a + b = 1
{ 4a + b = -2
Из
Из 2 уравнения вычитаем 1 уравнение:
a
a = -3
b
b = 1 - 3a = 1 - 3(-3) = 10
Б
Б) z3 = -3 + i; z4 = 2 - 3i
z4
z4 - z3 = 2 - 3i + 3 - i = 5 - 4i
(z4 - z3)/z4 = (5-4i)/(2-3i) = (5-4i)(2+3i) / ((2-3i)(2+3i)) =
= (10-8i+15i+12) / (4+9) = (22+7i)/13
Re
Re ((z4-z3)/z4) = 22/13
Im
Im ((z4-z3)/z4) = 7/13
2) (10+x)(x-10)-(x+3)²= x²-100-(x²+9+6x)= x²-100-x²-9-6x=-6x-109
3) (9-x)(x+9)-(x-7)²=81-x²-(x²+49-14x)= 81-x²-x²-49+14x= -2x²+32+14x
4) (3+x)²-(x-3)²= (3+x-(x-3))(3+x+x-3)= (3+x-x+3)*2x= 6*2x=12x
5) 2(a+4)²-(8+x)(x-8)= 2(a²+16+8a)-(x²-64)= 2a²+32+16a-x²+64= 2a²+16a-x²+96